“FROM TANGIBLE SPACE TO INTANGIBLE SPACE“ KANOMAN PALACE AND KACIREBONAN PALACE - Ina Helena Agustina (SAMPURASUN, 2017)
Physical space or called tangible spaces are spaces that can be physically captured by the senses while nonphysical or intangible space is a space that is not caught by the senses. Anthropological research argues that the first 'double built' space is a physical building and the second is a result of interpretation of taste and imagination (Gieryn, in Short, 2015). Kanoman palace and Kacirebonan palace is a palace located in the city of Cirebon. The two palaces not only physically still have the form of a palace building but also still have mystics believed by the community as an integral part of human life. The purpose of this paper is to show tangible space and intangible space in both palaces as part of the meaning of the palace. The method used is the research method of Husserl phenomenology and conducting the review literature from the results of the themes that appear especially space in both palaces. The result shows that these two palaces have different spatial arrangements and different building arrangements but the direction of the northward winds into the sacred position of the palace. The position is related to the position of the tomb of Sunan Gunung Jati as an ancestor and founder of the palace in Cirebon. The position is manifested as intangible space palaces in Cirebon.